Respectus Philologicus, 2010 Nr. 18 (23) - Bankauskaitė, Gabija (Respectus Philologicus, 2010)
CONTENTSI. PROBLEMS AND SOLUTIONSIsabel Íñigo-Mora, Gloria Álvarez-Benito (Spain). Gestures and Words in Political Discourse: a Case Study of the Obama-McCain Encounter... 11Vadim V. Dementyev (Russia). Anecdote in the Era of Censorship: Types of Public Representation (Experience of Diachronic Analysis of Anecdots on the Material of the Magazine Krokodil)... 26Daiva Aliūkaitė (Lithuania). New Dialect: the Possible Scenario of Dialectal Discourse Estimation...41Marek Ruszkowski (Poland). Krylov Law in Polish Linguistic Research...58II. FACTS AND REFLECTIONSLoreta Ulvydienė (Lithuania). Literature after 9/11: John Updike’s Terrorist...64Fryderyk Listwan (Poland). Comment on Intertextuality: Allusion in Leonid Leonov’s Publicistic Writings... 74Inesa Šeškauskienė (Lithuania). Who Discusses: the Paper or the Author of the Paper? Inanimate Subject + Active Verb in Lithuanian Linguistic Discourse as Compared to English...83Eleonora Lassan (Lithuania). On some Phenomena of Modern Russian Rhetoric in Public Communication (Rhetoric of Nostalgia as a Result of a Dialogue with the Past)...100Maria А. Sivenkova (Belarus). ‘Again, a Stupid Question!’ or How Politicians Criticise the Questions they are Being Asked...111Gayane R. Vlasyan (Russia). Communicative-Pragmatic Peculiarities of Counter-Questions in English Dialogical Discourse...126Jolanta Vitkauskienė (Lithuania). A Way of Analyzing Perlocutionary Speech Acts...135Gabija Bankauskaitė-Sereikienė, Justina Vaitelytė (Lithuania). Cultural Values in the Advertisements of New Romuva (1931–1940)...145Lina Inčiuraitė (Lithuania). Conceptual Metaphors of Sawel in Ælfric’s Catholic Homilies...159Liudmila Arcimavičienė (Lithuania). Cognitive Approach to language teaching. Cultural reality through Metaphor: a Case Study of Birthday Wishes...170Liudmila Garbul (Lithuania). Reflection of Results of Interslavonic Language Contacts in the Russian Chancery Language of the First Half of the 17th Century (Synchronic and Diachronic Aspects)...179Audronė Gedžiūtė, Jadvyga Krūminienė (Lithuania). A Semiotic Attempt at the Reconstruction of Celtic Mythical Models: the Figure of the Horse...191Danguolė Melnikienė (Lithuania). Are Onomatopoeic Interjections Necessary in a Bilingual Dictionary?...202Laura Kamandulytė-Merfeldienė (Lithuania). The Usage of Colour Terms in the Early Childhood...212Nijolė Tuomienė (Lithuania). Southern Aukštaitian Dialect in Belarus: the Result of Language Interplay...223Rima Bacevičiūtė (Lithuania). Features of Žemaitian Dialect of the Lithuanian Language in the Western Aukštaitian Subdialect of Kaunas...235Lidija Kaukėnienė (Lithuania). The Duration of Long Vowels in Standard Latvian...244III. OPINIONOleg Leschak (Poland). Methodological Character of Scientific Translation (Footnotes of Ferdinande de Saussure’s De l'essence double du langage. Translation into the Polish Language)... 252IV. OUR TRANSLATIONSBernard Sypniewski (USA). Snake in the Grass. Part I. Translated by Jurga Cibulskienė...265V. SCIENTIFIC LIFE CHRONICLEBooks reviewsLeonid P. Krysin (Russia). LUCIŃSKI, Kazimierz, 2009. Языковые заимствования и ментальность...273Dagnė Beržaitė (Lithuania). On English Dostoevsky in Lithuanian. MORRIS, R. N., 2009. Švelnus kirvis. MORRIS, R. N., 2009. Kerštingas potroškis...274Viktorija Makarova (Lithuania). On the most Important of all Arts. ARLAUSKAITĖ, Natalija, 2010. Trumpas feministinės kino teorijos žinynas... 278Vilnius University Kaunas Faculty of Humanities: journal of scientific life Giedrė Lankutytė (Lithuania). Advertisement Creators Accept START! Challenge...279In MemoriamУмер Аркадий Бартов... 282Arkady Bartov dies... 283Announce...284VI. REQUIREMENTS FOR PUBLICATION...285VII. OUR AUTHORS...293
Keywords: none